The Use of Digital Media as a Da'wah Tool in Sejuta Pemuda Mosque - Kholifah, Nur; Hikmah, Alfiah Nur (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2024)
Da'wah which aims to spread Islamic teachings requires a media that plays a role in supporting its success. This research aims to analyze the use of digital media as a means of da'wah by the Sejuta Pemuda Mosque, Sukabumi, West Java. This research uses a qualitative approach and collects data through interviews, observations, and documentation studies. The research results reveal that the Sejuta Pemuda Mosque uses digital media to promote itself as a solution-oriented mosque that addresses the congregation's needs in line with its functions and roles. The digital media used as a means of da'wah are Instagram and TikTok to inform various da'wah programs and content in mosques. The challenges faced include negative comments from online congregations, a shortage of human resources, and difficulties in generating creative ideas for preaching content. Despite these issues, digital media offers mosques the opportunity to enhance their role as effective missionary centers in the modern era.